A DESCRIPTION OF RISK FACTORS OF RECCURENT FEBRILE SEIZURE ON PEDIATRIC PATIENTS IN ABDUL WAHAB SJAHRANIE HOSPITAL IN SAMARINDA - Jessica Manaek Manika; Eva Rachmi (Universitas Muhammadiyah Kalimantan Timur, 2020)
Febrile seizures are the most common seizures in children. One-third of the children could develop a recurrent febrile seizure, with 75% of the recurrence occurring in the first year after the initial febrile seizure. The purpose of this study was to describe the risk factors of recurrence of febrile seizures on pediatric patients at Abdul Wahab Sjahranie Hospital in Samarinda. The research design was a descriptive study with cross sectional method. The sample of this study were children with febrile seizures whose age range were from 6 months to 5 years at Abdul Wahab Sjahranie Hospital in Samarinda from January 2017 to December 2018 who did not receive long-term prophylactic treatment for febrile seizures after the initial febrile seizure and did not experience intracranial infections, metabolic and electrolytes disorders, developmental delayed and cerebral palsy. The data were secondary data obtained from subject’s medical records. The study found recurrent febrile seizures occurred on 27 samples. In this study, recurrence of febrile seizures was more common on male patients (74%), the patients’ age majority were £ 12 months when experiencing initial febrile seizures (56%), as for the initial febrile seizures, they mostly experienced simple febrile seizures (59%) and fever with £ 24 hour interval in initial febrile seizures (63%). The collected data were tabulated by frequency and percentage and displayed in tables.